PENGARUH PERLAKUAN PADA BIJI DAN SUHU PENGEMPAAN TERHADAP SIFAT FISIKO KIMIA MINY AK KEMIRI - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1994)
The objective of this research is to study the effect of treatments on seed and pressing temperatures on candle nut oil properties. The treatments consisted of steaming, dry-frying and control. The candle nut seed having been treated was pressed at temperatures of 65and 135°c. The data obtained  were analysed by using fac.torial  design and the difference between means were tested with the LSD procedure, calculated with SAS program.Vie results showed that an increase in a pressing temperature caused a decrease in a peroxide number and an increase in an iod number. The  dry frying treatment on seed before pressing activities produced a few deterioration on candle nut oil, denoted by a high value of iod number and a small value of peroxide and saponification numbers.  Compared to a steaming treatment or a control, the dry frying  treatment gave a better quality on candle nut oil indicated by a higher value of  iod number. .